Sentiment Ideology: Membaca Pemikiran Lewis A. Coser dalam Teori Fungsional tentang Konflik (Konsekuensi logis dari Sebuah Interaksi di antara Pihak Jamaah LDII dengan Masyarakat sekitar Gading Mangu-Perak-Jombang) - Limas Dodi (Al-'Adl, 2017)
In a conflict, no institution is competent and acknowledged to be mediators. That isto say, conflict can be settled down if there are other parties as mediators, whetheras religious leaders or the ruling government, all of which is limited to stopping thedispute. The emergence of an Islamic thought and movement, although it isconsidered controversial, should not be judged as it is. Judging LDII as a hereticfor reasons that are generated by public. They are confident that LDII is an officialorganization and is protected by law. However, LDII until now has never issuedany book to read by public as the true information. In Coser's theory there are 4things related to the function of conflict. Firstly, that conflict between groupsincreases internal solidarity. Secondly, conflicts within the group have aninevitable antagonism that marks all social relationships. Thirdly, conflict increasesthe development of social bonds between groups. Fourthly, conflict is a majorstimulus to achieve social change.